Monitoring load, wellness, and psychological variables in female and male youth national team football players during international and domestic playing periods - Andersen, T. R.; Kästner, B.; Arvig, M.; Larsen, C. H.; Madsen, E. E. (Frontiers in Sports and Active Living, 2023)
Aim To study differences in total load exposure, wellness, and psychological variables in youth female (N = 19) and male (N = 20) national team football players during domestic and international playing periods, respectively.